Impact of storage temperatures and modified atmospheres on quality of fresh-peeled garlic cloves - Tanamati, F. [UNESP]; Hong, G.; Cantwell, M. I. (International Society for Horticultural Science (ISHS), 2016)
Fresh-peeled garlic is an increasingly important product for foodservice and retail markets. Two storage tests were conducted using garlic cloves ('California Late') that were peeled and packaged commercially. In Test #1 (MAP bags of 454 g), O2 concentrations averaged 15, 10 and 5% at 0, 5 and 10°C, respectively; the corresponding CO2 concentrations averaged 8, 15 and 23%. In Test #2 with small vacuum packed bags (30 g) inside larger master packages (170 g), atmospheres in the former averaged 1.5-3% O2 and 20-30% CO2 at all storage temperatures (0, 2.5, 5 and 7.5°C), while the master bags averaged 20-21% O2 and 0.5-0.8% CO2. In both tests, discoloration occurred in areas damaged during mechanical peeling, and was associated with lower L∗ and increased chroma values. In Test #1, decay was a significant contributor to loss of quality. In Test #1 excellent visual quality was maintained during 21 and 16 d at 0 and 5°C, respectively, and acceptable quality was maintained for about 10 d at 10°C. In Test #2, very good visual quality was maintained up to 28 d at 0 and 2.5°C, and acceptable quality was maintained for 21 d at 5 and 7.5°C. No important changes in texture were observed due to temperature or storage time. Pungency (thiosulfinate and pyruvate concentrations) decreased with time and the decrease was greater at higher storage temperatures. A reasonable expected storage-life of commercially peeled and modified atmosphere packaged garlic is 3-4 weeks at 0°C, 2-3 weeks at 5°C and 1-2 weeks at 10°C.
Keywords: Color; Dry weight; Pungency; Storage-life; Visual appearance